EFEKTIVITAS PEMBELAJARAN MATEMATIKA KONTEKSTUAL DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK SEKOLAH DASAR - Mansur Mansur (Jurnal keilmuan dan Kependidikan dasar, 2019)
The purpose of this study is to examine differences in increasing understanding of mathematical concepts between students who learn using a contextual mathematics approach and students who use conventional learning. The quasi-experimental method was chosen with a pretest-posttest control group design. The research sample is the fourth-grade students of East Bekasi Elementary School, Bekasi City, West Java. Mathematical understanding tests, observation sheets, and interview guides are the instruments used. Data obtained from interviews and observations were analysed descriptively to determine students' responses to learning and see the implementation of learning and students' activities in learning. Data on students' understanding of mathematical concepts were examined through descriptive statistics and inferential statistical tests to calculate the effect size. The results of the study show that there is a significant difference in increasing understanding of mathematical concepts between students who are treated with contextual mathematics learning and students who take conventional mathematics learning. No interaction was found between learning factors and school level on increasing understanding of mathematical concepts. The results of the calculation of the effect size confirm that the effect size of the study can be categorized as a large criterion